Climate justice for the southwestern coastal region of Bangladesh - Ashrafuzzaman, Md (2022)
Climate change is considered a moral, ethical and social issue, which makes it dierent from other developmental issues. The foremost instance of lack of justice regarding climate change is that the worst impacted areas are the ones with the lowest contribution to greenhouse gas emissions, such as the southwestern coastal region of Bangladesh (SWCRB). Climate change is principally triggered by the presence and eventual spread of industrialization. This study employed themixedmethod, combining qualitative and quantitative methods of data collection and analysis for development of a framework for climate justice. Data and information were obtained from both primary and secondary sources. In primary sources, quantitative data were collected from climate vulnerable community households using a structured close ended questionnaire and interactive sessions such as focus group discussions, in-depth interviews, key informant interviews, workshops, and case studies. This study explored the perceptions of people in the SWCRB, currently experiencing devastating eects of climate change and sea level rise including extreme natural disasters, seasonal changes, flooding, salinization, riverbank erosion, and water logging. These climate-induced changes are causing loss of housing, livelihoods, and land to the natives, in addition to a lack of access to proper nutrition, potable water, and healthcare thus exacerbating social injustice. A capability-based approach to climate justice is introduced in this paper, which allows for residents of this region to prepare and rebuild their own communities and create adaptive mechanisms based on their specific capabilities.